Nursing care in the patient with diabetes mellitus from the practice of self-care (Boletín Semillero de Investigación en Familia, 2023)
Introduction: the practice of self-care is a fundamental factor in the macrotreatment of patients with type 2 diabetes mellitus, from which the individual acquires skills in the acquisition of knowledge, attitudes and practices. Objective: to analyze nursing care in patients with diabetes mellitus from the practice of self-care. Materials and methods: type of investigation: quantitative, descriptive. A search was carried out for research carried out at an international and national level from different disciplines, especially nursing. Results: it is evidenced that people aged 27-59 present the highest percentage of diabetes mellitus among youth, with a percentage of 4%, and at the same time with 25%. In the surveyed population, it is highlighted that the majority of people are male, with 54%, followed by females, with 46%. It is noticed that 50% of the population surveyed is married. Conclusion: to conclude, it is important to emphasize the nursing work in the mental and physical care of these patients. Self-care practice is an essential component of diabetes treatment.
Keywords: self-care; nursing care; diabetes; education.